2008
DOI: 10.1111/j.1742-481x.2007.00405.x
|View full text |Cite
|
Sign up to set email alerts
|

Povidone–iodine: use in hand disinfection, skin preparation and antiseptic irrigation

Abstract: Iodine and its antibacterial properties have been used for the prevention or management of wound infections for over 150 years. However, the use of solutions (tincture) of iodine has been replaced by the widespread use of povidone-iodine, a water-soluble compound, which is a combination of molecular iodine and polyvinylpyrrolidone. The resultant broad spectrum of antimicrobial activity is well documented and its efficacy, particularly in relation to resistant micro-organisms such as methicillin-resistant Staph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
139
0
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(148 citation statements)
references
References 98 publications
(132 reference statements)
2
139
0
7
Order By: Relevance
“…This includes residents from the commonly studied genus Staphylococcus, often chosen for its ease of use in culture-based experiments (46,47). In line with these findings, we also observed a decrease in Staphylococcus residents in our sequencing and culture studies.…”
Section: Discussionsupporting
confidence: 80%
“…This includes residents from the commonly studied genus Staphylococcus, often chosen for its ease of use in culture-based experiments (46,47). In line with these findings, we also observed a decrease in Staphylococcus residents in our sequencing and culture studies.…”
Section: Discussionsupporting
confidence: 80%
“…It could be observed that longer incubation of HCV with PVP-I resulted in decreased amounts of core protein (data not shown), suggesting that this disinfectant has a direct effect on the viral capsid and therefore simultaneously on the viral envelope. The antimicrobial mechanism of PVP-I has been described as a direct delivery to the bacterial cell membrane, where it rapidly penetrates into the microorganism and targets key groups of proteins, nucleotides, and fatty acids in the cytoplasm and cytoplasmic membrane (38). The antiviral action against viruses has not been extensively studied, but it is likely that iodine attacks the surface proteins of enveloped viruses; it could also destabilize membrane fatty acids by reacting with unsaturated carbon bonds (39).…”
Section: Discussionmentioning
confidence: 99%
“…Both the actions of Triton X-100 and of PVP-I are thought to occur by targeting of the viral envelope. Triton X-100 is a nonionic surfactant commonly used as a detergent in laboratories that solubilizes proteins of the cell membrane (37), whereas PVP-I is a complex of iodine and a solubilizing carrier, which acts as a reservoir of "free" active iodine (38). With both inactivation methods, we observed a mild reduction in the ability of the RNA to replicate after the transfection of virusassociated genomes, indicating that both treatments have an influence on the viral RNA.…”
Section: Discussionmentioning
confidence: 99%
“…PVP-I, a combination of molecular iodine and polyvinylpyrrolidone, has replaced the solution (tincture) of iodine widely used in clinical practice (17). PVP-I is an example of an iodophor that acts as a conservator of free active iodine (18).…”
Section: Discussionmentioning
confidence: 99%